ORGANIZING EXPERIENTIAL ACTIVITIES TO DEVELOP DIGITAL CAPABILITIES FOR PRIMARY SCHOOL STUDENTS - Thi Lan Anh, Vu; Phuong Anh, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2025)
Organizing experiential activities in primary schools is one of the effective ways to develop students’ digital capabilities for students. Through participation in practical situations, students use digital tools and platforms to solve age-appropriate problems. Such experiential activities support not only the acquisition of basic digital skills but also the development of digital thinking and the ability to apply technology in everyday contexts. The article presents the theoretical foundations and outlines a structured process for organizing experiential activities in primary schools to support the development of students’ digital capabilities.